Peer Review : Upaya Meningkatkan Kualitas Jasa Firma Akuntan Publik - Widiastuti, Harjanti (Journal of Accounting and Investment, 2002)
In recent years, most people ask qualities of CPA firmâ€™s work in accounting and auditing services. In response to the call for more accountability, public accountants should make â€œauditâ€ or review to their work and disclose more detail their operations. In 1977, the Amarican Institute of Certified Public Accountants (AICPA) established a review mechanism referred to as â€œpeer reviewâ€ or some people called â€œauditorâ€™s auditâ€ The result of Maier and Fuglisterâ€™s survey indicated that peer review program is perceived by auditors as one of the most important appraisal activities to improve audit quality. Depart from their survey, this article describe a simple explanation concerning quality control system as a background and guidance to perform peer review, peer review concept itself and how audit quality can be improved through peer review.